Masterpieces East & West : from the collection of the Birmingham Museum of Art. - Birmingham Museum of Art, Birmingham; Adams, E. Bryding; Albainy, Tracey; Antoon, Donna; Baker, Nila A.; Eagan, Walton; Elsas, Ellen Friend; Friedman, Ann; Gover, Mary; Harris, Suzan B.; Herrington, Carson; Hurley, Ann; et al. (Birmingham : Birmingham Museum of Art, 1993)
Wright, Frank Lloyd ; Severini, Gino ; Kollwitz, Kathe ; Lalique, René ; Abbott, Berenice ; Archipenko, Alexander ; Nevelson, Louise ; Lipchitz, Jacques ; Dali, Salvador ; Marini, Marino ; Frankenthaler, Helen ; Stella, Frank ; Lawrence, Jacob ; Guston, Philip ; Charlesworth, Sarah ; Caro, Anthony ; Arneson, Robert ; Botero, Fernando ; John, Isabel ; Greenblat, Rodney Alan ; Wiley, William T. ; Frank, Robert ; Rivers, Larry ; Nutt, Craig ; Chin, Mel ; Sherman, Cindy
English
boek